Spectrophotometric Estimation of Propranolol in Tablet Dosage Form - BHANDARI, ANIL; KUMAR, BRIJESH; PATEL, RAKESH (Asian Journal of Chemistry, 2010)
A simple and accurate spectrophotometric method has been developed for the quantitative estimation of propranolol in bulk and tablets. The method is based on the reaction of propranolol with 1-chloro-2,4-dinitrobenzene, forming a complex, which is analyzed by spectrophotometry. The absorbance maxima (λmax) was found to be 314.6 nm. Optimization of reaction was carried out with the factors, temperature, time, stability of complex, molar ratio of drug: reagent. The proposed method was validated as per ICH guidelines.